THE EFFECT OF HUMAN RELATIONS, WORK ENVIRONMENT, AND ORGANIZATIONAL CULTURE ON WORK ETHICS (Study of Manufacturing Companies in Indonesia) - Suryadi Suryadi; Anthonius Yanto Gebang (UPMI Management, 2022)
Study this aim to know the influence of human relations, environment, physical work, and organizational culture on the work ethic at the Injection PT. Yasunli Eternal Main Plastic. The type of study used is quantitative. They are using observation data collection techniques, questionnaires, and literature study. Method taking sample use probability sampling, which manifold simple random sampling and sampling conducted on 150 employees of the Injection PT. Yasunli Eternal Main Plastic. To determine the number of samples, use the formula slovin. Method analysis used is test validity, test reliability, classical assumption test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, and hypothesis testing, T-test. From the research results, the variables of Relations, Physical Work Environment, and Organizational Culture partially have a positive and significant effect on the work ethic variable. JEL Classification: L20, L25, M12